PATRIARKI SEBAGAI PEMICU KEKERASAN RUMAH TANGGA PERSPEKTIF GENDER - Azizah, Fasya; Jannah, Shofiatul (Institut Agama Islam Negeri (IAIN) Syekh Nurjati Cirebon, 2025)
The study examines the role of patriarchate in triggering domestic violence, focusing on the gender aspect. The study USES an interdisciplinary approach to analyze how patriarchate norms strengthen gender inequality and create an environment that encourages growing violent behavior. Through literature and field work, this study reveals the impact that patriarchical institutions have on domestic relations and how the structure provides room for violence against women. It is hoped that this study will provide a deeper insight into the need for patriarchical treatment asan essential step in the prevention and treatment of gender-based domestic violence.We also discuss policy implications and intervention recommendations for building communities that are more equal and safer for all.